Advanced damage detection techniques in historical buildings using digital photogrammetry and 3D surface anlysis. - Galantucci, Rosella Alessia; Fatiguso, Fabio (Journal of Cultural Heritage, 2019)
Highlights • Non-destructive survey techniques, using digital photogrammetry to obtain 2D/3D models of an historical building. • Assessment of damages, through 3D surface analysis (mathematical/morphological operators). • Quantitative assessment and data about cracks, lacks, erosions on envelope surfaces through digital image processing. • Monitoring of the state of conservation of surfaces through the analysis of models deriving from acquisition at different times. • Implementation, in the field of Architectural Restoration, of software supports generally used for three-dimensional metrology and surface topography. Abstract In the last twenty years, advances in technology led to a progressive digitalization in photography and photogrammetry and to the development of a considerable number of image processing software. In several fields, Digital Image Processing techniques began to spread. For example, in Civil Engineering there are many methodologies for the monitoring of reinforced concrete structures or road pavements. In most cases they involve the application of mathematical and morphological filters to two-dimensional images, to obtain quantitative information about the decay of the analyzed structures. Instead in Architectural Restoration there are still few researches focused on these methodologies, because of the great complexity and uniqueness of historical buildings. Furthermore, until now architectural photogrammetry mainly concerned geometric survey and it was not widely used to diagnose the presence of alterations on buildings, despite the great potential of a non-invasive, contactless survey technique. Therefore, the aim of this research is to create an analysis approach, to detect damages on three-dimensional models, richer in information about depth and volume. The analysis can be carried out through a specific set of spatial and morphological filters for advanced surface analysis, adopting software tools mostly used for three-dimensional metrology and surface topography. A sequence of operations can be executed, allowing to obtain quantitative information about some kinds of alterations (cracks or features induced by material loss) from three-dimensional models like point clouds or polygonal meshes. The procedure was tested and validated on a case study (Palazzo Palmieri, Monopoli – Italy). The result of the research is a low interaction approach, through which it is possible to identify and quantify damages on the surfaces.